A draft genome sequence of an invasive mosquito: an Italian Aedes albopictus. (July 2015) - Dritsou, Vicky; Topalis, Pantelis; Windbichler, Nikolai; Simoni, Alekos; Hall, Ann; Lawson, Daniel; Hinsley, Malcolm; Hughes, Daniel; Napolioni, Valerio; Crucianelli, Francesca; Deligianni, Elena; Gasperi, Giuliano; et al.
Abstract : The draft genome sequence of Italian specimens of the Asian tiger mosquito Aedes (Stegomyia) albopictus (Diptera: Culicidae) was determined using a standard NGS (next generation sequencing) approach. The size of the assembled genome is comparable to that of Aedes aegypti ; the two mosquitoes are also similar as far as the high content of repetitive DNA is concerned, most of which is made up of transposable elements. Although, based on BUSCO (Benchmarking Universal Single-Copy Orthologues) analysis, the genome assembly reported here contains more than 99% of protein-coding genes, several of those are expected to be represented in the assembly in a fragmented state. We also present here the annotation of several families of genes (tRNA genes, miRNA genes, the sialome, genes involved in chromatin condensation, sex determination genes, odorant binding proteins and odorant receptors). These analyses confirm that the assembly can be used for the study of the biology of this invasive vector of disease.